Clinical impact of free dorsal interosseous flap combined with tendon graft on function recovery in one-stage reconstruction of composite dorsal wrist soft tissue defects - Shi, Lingling; Ding, Luobing; Zhang, Jianping; Su, Ruilong; Shi, Weifa; Guo, Zhiming (Frontiers in Surgery, 2025)
BackgroundThis study aimed to clarify the clinical efficacy of the free dorsal interosseous flap (DIOF) combined with tendon grafting in one-stage reconstruction of composite dorsal wrist soft tissue defects, and comprehensively evaluate the survival rate of the flap, wrist joint function recovery, and subjective experience of patients.MethodsA retrospective study was conducted on 28 patients (18 men and 10 women) with composite dorsal wrist defects (size, 5 cm × 8 cm–14 cm × 10 cm, involving 3–5 extensor tendons) treated between January 2019 and June 2023. All patients underwent one-stage reconstruction using the free DIOF with tendon grafting. In addition to these conventional evaluation indicators [flap survival rate, wrist total active motion (TAM), grip strength recovery, DASH scores, Mayo scores, and sensory recovery], high-frequency ultrasound tendon healing evaluation, laser Doppler flap blood flow monitoring, wrist stability test, and Likert scale satisfaction survey were added. The patients were followed up for 12 months and analyzed using a multi-dimensional evaluation system.ResultsThe flap survival rate was 95.2% (27/28), with one case of partial necrosis healing after a dressing change. At 12 months, TAM reached (112.5 ± 11.8)°, grip strength recovery was (83.7 ± 7.5) %, DASH scores improved to (13.2 ± 3.5) points, and Mayo scores depicted excellent/good outcomes in 85.7% (excellent 15, good 9). Sensory recovery achieved S3+-S4, with 64.3% of cases exhibiting two-point discrimination <10 mm. The stable rate of flap blood perfusion was 96.4%, the excellent and good rate of wrist joint stability was 89.3%, and patient satisfaction score was (9.2 ± 0.8) points.ConclusionOne-stage reconstruction using free DIOF combined with autologous tendon grafting effectively facilitates wrist joint function recovery, demonstrating satisfactory clinical outcomes.